Overview of Integrated Antenatal Care (ANC) Implementation in the Regional Technical Implementation Unit West Selemadeg Health Center Tabanan Regency - Ni Luh Putu Ayu Seprianti; Ni Komang Erny Astiti; Listina Ade Widya Ningtyas (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
Providing comprehensive and quality ANC services to pregnant women is called Integrated ANC services. The indicator used to describe pregnant women's access to antenatal care is K1 coverage while the indicator to describe service quality is K4-K6 coverage with 10T service quality including physical examination, laboratory examination, provision of fe table, immunization and counseling. The purpose of the study was to determine the description of the application of integrated antenatal care (ANC) in the Regional Technical Implementation Unit of the West Selemadeg Health Center. This type of research is descriptive quantitative. Implementation of research in March - April 2024 with purposive sampling technique. The sample using the slovin formula amounted to 40 people. Data collection in the form of integrated ANC indicator data collection sheets. Data analysis using univariate in the form of frequency distribution. The results showed that pure K1, K4 and K6 visits from pure K1 were 62.5% of respondents while a small proportion of respondents according to the standards of K1 access visits, K4 and K6 from K1 access were (37.5%) respondents. The results of pure K1, K4 and K6 services from pure K1 were 62.5% of respondents while a small proportion of respondents met the standards of K1 access visits, K4 and K6 from K1 access as many as (37.5%) respondents. Suggestions for UPTD Puseksmas Selemadeg Barat to increase education to pre-conception couples and pregnant women about the purpose of visits and appropriate ANC examinations.